Penerapan Biopori Pada Area Halaman Gedung SMK Farmasi Maharani - Endang Larasati; Yudha Rachman Winarto; Setiyono (Jurnal Pengabdian Kepada Masyarakat (JPKM) Langit Biru, 2022)
The courtyard of the Pharmacy Vocational School Building experiences flooding during the rainy season and reduced drought during the dry season due to limited water catchment areas due to limited land. In this community service activity (PkM), the goal is to provide knowledge to SMK residents about the application of bio-pore infiltration holes. The method of implementing this activity involved teachers and staff at the Maharani Pharmacy Vocational School. A biopori infiltration hole with a diameter of 10 cm and a depth of 100 cm is made, and inside it is filled with organic kitchen waste. This waste is one of the methods for producing compost that can be used by the community. The results of this PkM activity after 3 weeks of evaluation were significant changes. The application of the biopore infiltration hole technique has benefited the Pharmacy Vocational School Building and the surrounding community. In addition to overcoming flood and drought problems, this activity also contributes to reducing organic kitchen waste and producing useful compost.